Pengaruh Corporate Governance terhadap Kinerja Keuangan dengan Corporate Social Responsibility sebagai Variabel Mediasi pada Perusahaan Consumer Non-Cyclicals yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2022 - Lisa Andriani Putri; Erly Mulyani (Universitas Negeri Padang, 2024)
This study intends to examine impact of corporate governance on financial performance with corporate social responsibility as an mediating variable. The scope of the study encompasses companies in the consumer non-cyclical sector, with a selected sample of 32 firms using purposive sampling methodology. The study involves analyzing 113 companies listed on the Indonesia Stock Exchange during the period from 2018 to 2022. Secondary data is employed for analysis, and the SEM-PLS method is applied. Based on the result, corporate governance exhibit a substantial and beneficial impact on both financial performance and corporate social responsibility while corporate social responsibility demonstrates a minor positive influence on financial performance, so that corporate governance can’t mediate the relationship between corporate governance and financial performance.